THE LIQUID LINE OF DESCENT OF ANHYDROUS, MANTLE-DERIVED, THOLEIITIC LIQUIDS BY FRACTIONAL AND EQUILIBRIUM CRYSTALLIZATION--AN EXPERIMENTAL STUDY AT 1.0 GPA - Villiger S.; Ulmer P.; Muntener O.; Thompson A.B. (My University, 2004)
Two series of anhydrous experiments have been performed in an end-loaded piston cylinder apparatus on a primitive, mantle-derived tholeiitic basalt at 1.0 GPa pressure and temperatures in the range 1060–1330°C. The experimental data provide constraints on phase equilibria, and solid and liquid compositions along the liquid line of descent of primary basaltic magmas differentiating in storage reservoirs located at the base of the continental crust. The first series are equilibrium crystallization experiments on a single basaltic bulk composition; the second series are fractionation experiments where near-perfect fractional crystallization was approached in a stepwise manner using 30°C temperature steps and starting compositions corresponding to the liquid composition of the previous, higher-temperature glass composition. Liquids in the fractional crystallization experiments evolve with progressive SiO2 increase from basalts to dacites, whereas the liquids in the equilibrium crystallization experiments remain basaltic and display only a moderate SiO2 increase accompanied by more pronounced Al2O3 enrichment. The principal phase equilibria controls responsible for these contrasting trends are suppression of the peritectic olivine + liquid = opx reaction and earlier plagioclase saturation in the fractionation experiments compared with the equilibrium experiments. Both crystallization processes lead to the formation of large volumes of ultramafic cumulates related to the suppression of plagioclase crystallization relative to pyroxenes at high pressures. This is in contrast to low-pressure fractionation of tholeiitic liquids, where early plagioclase saturation leads to the production of troctolites followed by (olivine-) gabbros at an early stage of differentiation.